ENGANGING STUDENTS ATTENTION BY USING DISCOURSE MAKERS: STUDY OF LECTURER-STUDENTS INTERACTION IN ENGLISH CLASS DISCUSSION - Radius Setiyawan; Sri Lestari (Proceedings Education and Language International Conference, 2017)
Discourse markers were important part within the scope of the study of classroom interaction. The theme of this research was the use of discourse markers. Research on discourse markers was a small component in the basic research discusses about the various habits of a teacher's question, the function of teachers talk, and teacher’s talk structure. This study took a sample of English learning activities at the University of Indonesia. Learning was attended by 29 students from various departments at the Science Faculty and one lecturer with experience more than three years. This study would browse the variety and functions of discourse markers that appear in the lecturer-students interaction conducted by discussion activities. The collection of information was done through observation of the lecturer-students interaction during the learning process. Observations carried out electronically by using an audio recorder via laptops and mobile phones. Then, I did the coding and transcription of the data. The analysis described that there were several types and classifications of discourse markers with diverse pragmatic functions. Discourse markers that had a high frequency in use by lecturers was "okay" that often has different pragmatic function. The variety of discourse markers used by lecturers in this discussion activity observation were often used to show understanding, to confirm understanding and ask students to do turn argued.Keywords: clasroom interaction, discourse makers, english language learning